Perspective by incongruity or cynicism? An analysis of redaction and framing in The Daily Show with Jon Stewart's "Armadebton 2011" - St. Clair, Alita L., author; Carcasson, Martín, advisor; Lupo, Jon, committee member; Mallette, Dawn, committee member (Colorado State University. Libraries, 2012)
At the 2006 National Communication Association convention, Rod Hart and Johanna Hartelius presented a paper in which they charged Jon Stewart with sins against democracy. The transcript of the "trial," including arguments in defense of Stewart that were provided by Lance Bennet and Rob Hariman, was published in a 2007 critical forum in Critical Studies in Media Communication. This thesis extends that conversation to consider whether The Daily Show with Jon Stewart's redaction strategies and framing practices may improve or undermine audiences' political engagement. First, through rhetorical analysis, this thesis shows how The Daily Show's use of redaction potentially strengthens the conditions for democracy by performing a watchdog role and diversifying political discourses in the public sphere. Conversely, through framing analysis, this thesis reveals that the pervasiveness of strategy framing on The Daily Show may contribute to cynical interpretations of political life and therefore decrease political engagement among audiences. Finally, this thesis points to areas for future research into issues surrounding media and democracy and argues for the advancement of a more deliberative model for political news that would increase audiences' perceived political efficacy.
Keywords: deliberation; democracy; media framing; perspective by incongruity; political cynicism; redaction